2011
DOI: 10.1111/j.1365-2362.2011.02476.x
|View full text |Cite
|
Sign up to set email alerts
|

Volume regulating hormone responses to repeated head-up tilt and lower body negative pressure

Abstract: We speculate that the observed differences in blood pressure and hormonal responses to LBNP and HUT are caused by divergent effects of blood pooling in the splanchnic region, despite similar reductions in splanchnic perfusion. Apparently with repeated central hypovolaemia, especially by the 3rd application of stress, plasma aldosterone levels rise (along with ACTH), conceivably increasing its volume-guarding effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…This implies a dissociation of the aldosterone level and renin response under the particular conditions of parabolic flight. Interestingly, dissociation of plasma aldosterone levels and plasma renin activity has previously been reported in subjects experiencing presyncope and in subjects undergoing repeated orthostatic challenges by tilt table testing and lower body negative pressure (LBNP) tests (Roessler et al 2011; Hinghofer-Szalkay et al 2011). The works of Roessler et al and Hinghofer-Szalkay et al indicate furthermore that during orthostatic challenge aldosterone is rather controlled by adrenocorticotropic hormone (ACTH) than by renin, which may serve as an explanation of the dissociated aldosterone–renin response in parabolic flight.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This implies a dissociation of the aldosterone level and renin response under the particular conditions of parabolic flight. Interestingly, dissociation of plasma aldosterone levels and plasma renin activity has previously been reported in subjects experiencing presyncope and in subjects undergoing repeated orthostatic challenges by tilt table testing and lower body negative pressure (LBNP) tests (Roessler et al 2011; Hinghofer-Szalkay et al 2011). The works of Roessler et al and Hinghofer-Szalkay et al indicate furthermore that during orthostatic challenge aldosterone is rather controlled by adrenocorticotropic hormone (ACTH) than by renin, which may serve as an explanation of the dissociated aldosterone–renin response in parabolic flight.…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that levels of AVP and cortisol are extensively increased in motion sickness; therefore, the CT- pro AVP and cortisol values of the motion-sick subjects were excluded from the statistical analysis of the blood hormones, and individual data are shown instead. Furthermore, we did not analyze blood levels of ACTH what might had allowed us to identify a close relationship between ACTH and aldosterone in parabolic flight as it is known for orthostatic stress during tilting and LBNP (Roessler et al 2011; Hinghofer-Szalkay et al 2011). Fifth , rebreathings at 0 G z fell into the early 0 G z phases, which are characterized by a sympathetic withdrawal and acute activation of the vagal nervous system.…”
Section: Limitationsmentioning
confidence: 99%
“…These results may have clinical and spaceflight applications X [50] We speculate that the observed differences in blood pressure and hormonal responses to LBNP and HUT are caused by divergent effects of blood pooling in the splanchnic region, despite similar reductions in splanchnic perfusion. Apparently with repeated central hypovolaemia, especially by the 3rd application of stress, plasma aldosterone levels rise (along with ACTH), conceivably increasing its volume-guarding effect X [51] We conclude that during the 20-min supine post-syncopal period, plasma volume, plasma renin activity (PRA) and adrenomedullin and vasopressin (AVP) return closer to baseline but aldosterone and ACTH continue increasing.…”
mentioning
confidence: 78%
“…In [50], we reported that both adrenocorticotropic hormone and aldosterone progressively increased with repeated stresses and were elevated above baseline values during each rest period.…”
Section: Evsyukova)mentioning
confidence: 95%
See 1 more Smart Citation